Coping mechanism in overcoming food (in) security among the community at the Malaysia-Thailand border: A human security perspective - Ku Amir, Ku Nurasyiqin; Mat, Bakri (Kasetsart Journal of Social Sciences, 2021)
Food security is one of the components that form the basic needs of a nation, households, and individuals. Any disruption at the dimensions of availability, accessibility, utilization and stability of food security will threaten the security and wellbeing of citizens. Although food availability at the national level is guaranteed through local production and imports, the accessibility and utilization dimensions are not yet fulfilled as certain groups are still unable to access and utilize adequate food. Therefore, this research aims to examine the coping mechanisms adopted by Malaysian households among communities in the Malaysia-Thailand border area by using the human security approach. The study is conducted using a qualitative research method to collect and analyze both primary and secondary data. Primary data were obtained through official documents and an in-depth interview with key informants among Malaysian households of the communities near Malaysia-Thailand border, local leaders and academicians. Meanwhile, published materials and online documents such as books, journal articles and reports served as a secondary source of data. The findings indicate that the households adopted several coping mechanisms, as well as utilizing external assistance programs to reduce the impact of food insecurity. Coping mechanisms, which made a difference in reducing vulnerability to food insecurity, varied among households depending on resources available. However, these mechanisms should be further scrutinized by relevant agencies to understand long-term impact on the affected households. Realizing this fact, the government should consider adopting the human security concept, which emphasizes community empowerment as a framework in policymaking, with the aims to eradicate food insecurity among vulnerable households and to ensure the well-being of every Malaysian.